Expression of choline acetyltransferase mRNA in spermatogenic cells results in an accumulation of the enzyme in the postacrosomal region of mature spermatozoa. - Ibáñez, C F (1991)
The gene encoding choline acetyltransferase (ChAT; EC 2.3.1.6), the key enzyme in the synthesis of the neurotransmitter acetylcholine (ACh), is shown to be expressed in rat and human testes. High levels of two ChAT transcripts of 3.5 and 1.3 kilobases were detected by Northern blot analysis of adult rat testis RNA. A single ChAT mRNA species of 3.2 kilobases was detected in human testis. Cells responsible for the synthesis of ChAT mRNA in rat testis were localized by in situ hybridization in the middle part of the seminiferous epithelium, where the labeling was mostly found over spermatocytes and spermatids. Studies on the ontogeny of ChAT mRNA expression showed low levels in prepubertal rats with increasing levels as sexual maturation is reached. A peak of expression was seen at postnatal day 32, correlating with the onset of postmeiotic spermatogenesis. Results from surgical and pharmacological treatments suggest that androgens, as well as pituitary factors, could influence the relative levels of the two ChAT mRNAs detected in rat testis. Evidence for translation of the mRNA detected in the testis was obtained from the demonstration of ChAT-like immunoreactivity in ejaculated human spermatozoa. The staining was restricted to the postacrosomal region of the head, where the membrane of the sperm first fuses with that of the egg during fertilization, and to the annulus, a ring of dense material in the caudal end of the midpiece. Combined, these findings support the hypothesis that the neurotransmitter ACh is involved in reproductive function.